Pursed-Lips Breathing and High Fowler Position in Pleural Effusion Patient: Case Report - Janah, Syahratul; Platini, Hesti; Fitri, Siti Ulfah Rifaatul (Universitas Negeri Gorontalo, 2024)
Pleural effusion is a collection of fluid in the pleura caused by the impact of another disease. Treatment for pleural effusion can be provided through the nursing care process with airway management interventions to help minimize shortness of breath in patients. There are nursing actions that can be carried out independently by nurses, namely the semi-fowler or fowler position, administering additional oxygen, and other therapies such as pursed lips breathing. The aim of this research is to determine the effectiveness of the combination of pursed lips breathing and high fowler position in the nursing care process for patients with ineffective airway clearance nursing problems in patients with pleural effusion using the case report method and nursing care approach. The results of the study showed that the combination of pursed lips breathing and the use of the selected high fowler position as high as 90 degrees for 3 days provided comfort and reduced shortness of breath with pleural effusion while being balanced by the provision of pharmacological therapy. Providing pursed lips breathing therapy and high fowler position has the potential to reduce shortness of breath in patients with pleural effusion